Customer perception of logistics service quality using SIPA and modified Kano: Case study of Indonesian e-commerce - Ilyas Masudin; Yulyetha Kurnia Putri Hanifah; Shanty Kusuma Dewi; Dian Palupi Restuputri; Dwi Iryaning Handayani (Logistics, 2022)
Background: The success of e-commerce cannot be separated from a good delivery experience. Meanwhile, research that discusses the quality of logistics services that serve e-commerce by comparing the quality of its competitors in Indonesia is still little discussed. The case study in this research is two logistic service providers in Indonesia. Methods: This study uses the integration of the SIPA method and Kano Modification. Both SIPA and Kano can determine priority and effective strategies to improve service quality. Results: The use of SIPA can identify the importance of service attributes and compare the performance of the two logistics services. A dynamic cycle of service attributes encourages using Kano Modification in this study to expand opportunities for determining managerial strategies. Conclusions: The results in this study provide insight into the main strategies that must be carried out on attributes considered important and maintain quality to be superior to competitors.
Keywords: 650; logistics service; Modified-Kano; service attribute; SIPA grid